A Software Development Process Model for Gesture-Based Interface - Guimaraes, Marcelo de Paiva; Martins, Valeria Farinazzo; Ferreira Brega, Jose Remo [UNESP]; IEEE (Ieee, 2012)
Gesture-based applications have particularities, since users interact in a natural way, much as they interact in the non-digital world. Hence, new requirements are needed on the software design process. This paper shows a software development process model for these applications, including requirement specification, design, implementation, and testing procedures. The steps and activities of the proposed model were tested through a game case study, which is a puzzle game. The puzzle is completed when all pieces of a painting are correctly positioned by the drag and drop action of users hand gesture. It also shows the results obtained of applying a heuristic evaluation on this game.
Keywords: Human Computer Interaction; Human Factors; Software development; Gesture Interaction